ANALISIS KEBUTUHAN PENANGANAN SIMPANG EMPAT JALAN KARANGAWEN KM-18 DI KABUPATEN DEMAK - Irvan, Aditya Muhammad; Rizani, Mohammad Debby; Ariawan, Donny (Universitas PGRI Semarang, 2023)
The development of transportation in Demak Regency has an impact on increasing the movement of people, goods, and services. This is also very demanding for the improvement of transportation facilities and infrastructure in Demak Regency. This study aims to determine the performance of the uncited intersection of field conditions based on the 1997 MKJI guidelines, from the results of research in the field and the calculation of the Karangawen interchange interchange km 18 that the busiest traffic occurred on Sundays at 17.30-17.45 with a total traffic flow value of 1269 smp / hour, and obtained analytical data With an intersection capacity value of 1372.8 width of the interchange approach 2,821 fak tor road median adjustment with value 1, faktor city size adjustment with value 1, faktor road environment type adjustment by 0.85 faktor left turn adjustment by 1.170 faktor turn right adjustment by 0.233 Minor road ratio misrepresentation factor of 0.726 with a saturation degree of 0.924 interchange traffic delay of 56.54 seconds/smp,Â main road traffic delay of 13.66 seconds/smp, minor road traffic delay of 61.67 seconds/smp, interchange geometry delay of 4, interchange delay of 60.54 Seconds/smp and queue opportunity for lower limit of 21.26 And queue opportunity for upper limit of 34.249.So the Karangawen km 18 intersection needs improvement at the intersection because it is seen from the value of the degree of saturation based on MKJI guidelines if the saturation value 0.75 then there is a need for interchange improvement.